Marketing: Farmers Promulgates Cash Crops, Itinerary to Support Their Livelihood and Enhance Their Living Standard - Onessimos Shangdiar (Journal of Social Entrepreneurship Theory and Practice, 2021)
This paper is a briefing on the marketing and emergence of cash crops in the Indo-Bangladesh border, South West Khasi Hills District Meghalaya. It is solely aimed at understanding the inborn entrepreneurship skills of the particular sub-tribe of the Khasis called "War". They live in steep and sloppy mountains with moderate temperatures and receive sufficient precipitation throughout the year, which enables them to sustain their farming. Marketing is the heart core of every individual, regardless of any background and professionals. Marketing plays a very important role to the farmers, and everyone could enhance their standard of living due to the technique of commercialization. The Non-farmers can buy the food crops from the farmers through the role of business administration. It is pointless to have money without having a food supply. Thus, the commercialization of agricultural produce is highly required. Cash crops cultivation promotes economic growth and social growth; economically, people can generate income, put savings, and purchase physical capital. Socially they bridged with each other, helping one another, exchanging work, advising the younger ones, and imparting knowledge to one another, providing seeds and saplings to the have not. There is an evolution from practicing traditional crops, which can be consumed directly, to Cash crops, which need to be exported outside of the State through a marketing system with the intention to manufacture further for finished products.